Quality of life and functional disability in patients with interstitial lung disease related to Systemic Sclerosis - Lumetti, Federica; Barone, Lissette; Alfieri, Cristina; Silva, Mario; Serra, Valter; Delsante, Giovanni; Sverzellati, Nicola; Ariani, Alarico (Acta Biomedica Atenei Parmensis, 2015)
Background: Systemic Sclerosis (SSc) is a connective disease impairing respiratory function. SSc worsens patients’ Health Assessment Questionnaire (HAQ-DI), Short Form 36 Physical and Mental Component Summary (SF36-PCS and SF36-MCS). The aim of this work is to verify whether there is correlation between quality of life and lung interstitiopathy in SSc patients. Methods: SF36 and HAQ-DI were given to each patient (48 in all). Lung involvement was evaluated with Baseline Dyspnea Index (BDI), spirometry and pulmonary fibrosis radiological assessment (PFRA). Correlations between SF36, HAQ-DI and lung involvement severity were investigated with Spearman’s rank test. A p-value